The Icelandic Financial Meltdown: An Investigation into the Theoretical and Empirical Facets of the Banking Crisis - Deshpande, Tina (2010)
Recent decades have witnessed the proliferation of globalisation of financial markets creating profitable opportunities for banks while at the same time making them vulnerable to severe risks. The volatility of bank earnings and a number of major bank failures have highlighted the costs of a global financial system and solicited and beckoned for restructuring of regulatory systems around the world that can effectively manage the inherent risks involved in cross border activities. (Kapstein, 1989). Public officials are increasingly being tested on their efficacy in handling the convoluted and intertwined problem of having to extract the benefits of economic interaction and integration while pursuing rightful national objectives such as bank safety and soundness (Cooper, 1968). The phenomenal globalisation the world has witnessed has ushered in an era wherein public officials have been compelled to make tradeoffs between domestic regulation and international competitiveness (Kapstein, 1989). The Icelandic banking system witnessed spectacular growth and expansion in a very short span of time. This growth was funded by cheap foreign financing allowing for a rapid increase in assets from 100 to almost 900 percent of GDP from 2004 to the end of 2007. By 2008, as the global financial conditions experienced a progressive deterioration the Credit Default Swap (CDS) spreads of Icelandic banks began to rise to unprecedented levels. The Icelandic banks had become too large in relation to the Icelandic economy beyond the threshold wherein the Central Bank could provide support or aid in order to prevent a systemic failure. The banks consciously took advantage of a liberal regulatory environment, good credit ratings, and favourable global market conditions thus following a policy of rapid expansion. The European regulatory framework was conducive to this growth. This policy posed no immediate problem so long as global market conditions were benign. (Fridriksson, 2009) This paper primarily attempts to elucidate and consolidate the multifaceted problems of the Icelandic banking sector and deliberates on their culmination into crisis. It offers a multidimensional perspective on the crisis, its aftermath and ensuing implications. The recent global financial crisis has revealed apparent weaknesses in the stress testing exercises performed on financial institutions and systems around the world. Failures to detect vulnerabilities in the banking systems were particularly pronounced while assessing liquidity risk, as the stress tests that were conducted focused predominantly on solvency risk (Ong and Čihák, 2010). With the help of data retrieved from the now defunct banks in Iceland, this paper also attempts to compare the iii performance of various internationally operational banks, from countries with large banking sectors and an independent currency. Through this paper, an attempt is made to show that models used to identify the factors leading to banking crisis and determine the possibility of its occurrence do not necessarily need to be complex or overly sophisticated. During the years prior to the recent financial calamity, stress tests performed on several banking systems did not explicitly reveal any major indications inclined towards the possibility for banking failure.